An experimental Study of the Pathogenesis of Retinopathy of Prematurity as a Promising Direction of Search for New Medicinal Approaches to its Prevention and Treatment - L. A. Katargina; N. B. Chesnokova; O. V. Beznos; N. A. Osipova; B. V. Viter (Российский офтальмологический журнал, 2018)
An experimental study was performed to reproduce the model of oxygen-induced retinopathy (OIR) in young rats. This model is promising for the study of the pathogenesis of retinopathy of prematurity (ROP) and for the search of new approaches to the prevention and treatment of the disease. It was found that the total protein content in the vitreous was increased during OIR at all observation times, with a maximum reached on the day 14. The phasal character was revealed in the changes of the level of antioxidant activity (AOA): on the day 7 AOA of rats with OIR is no different from the control, on the day 14, it becomes 6.4 times higher than the reference level, and on the day 18 (when the oxygen is no more active) it is falling but still remains higher than the norm. These findings suggest that the permeability of the blood-retinal barrier is damaged during OIR, and confirm the important role of oxidative stress in the pathogenesis of ROP, the advisability of the correction of its parameters by introducing antioxidants in the combined treatment of ROP, and the need for a differentiated approach to the times of their application Russian Ophthalmological Journal, 2016; 1: 68-72.